ADOLESCENT-PARENT COMMUNICATION ON SEXUAL AND REPRODUCTIVE HEALTH IN RURAL NEPAL: A CROSS-SECTIONAL STUDY - Karki, Rajesh; Thapa, Sujata; Kaphle, Maheshor (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Effective communication between adolescents and their parents plays a crucial role in fostering healthy sexual and reproductive behaviors. Despite its importance, communication remains limited in Nepal. Purpose: This study aims to assess the prevalence and determinants of adolescent-parent communication on sexual and reproductive health (SRH) topics in rural Nepal. Methods: A cross-sectional study was conducted among 319 adolescents selected from 604 adolescents in the Jhimruk Rural Municipality, Nepal, in 2023. Participants were randomly selected using the lottery method. Data was collected using a self-administered structured questionnaire. Descriptive statistics were employed for categorical variables, while multivariate logistic regression identified factors influencing adolescent-parent communication on SRH. Statistical significance was set at p<0.05, and the analyses were performed using SPSS version 26. Results: Most respondents (79.9%) were below 18 years of age, with a mean age of 15.80 years (SD ±1.63). Most (93.4%) had good knowledge of SRH. However, the prevalence of adolescent-parent communication on sexual and reproductive health topics was only 58.6%, with only 4.7% communicating frequently on different SRH topics. The major reasons for not communicating included shame (41.6%) and cultural unacceptability (30.4%). Significant factors associated with adolescent-parent communication included respondents' age, sex, ethnicity, boyfriend/girlfriend status, knowledge of SRH, parental living status, and parental education and occupation. Conclusion: Although the adolescents demonstrated good SRH knowledge, the substantial gap in parent-adolescent communication underscores the need for targeted interventions. Strategies should focus on empowering adolescents to initiate conversations with parents and educate both parties about the significance of open dialogue in SRH.